Criminal Law Policy In The Application of Restorative Justice Principles In Tax Criminal Investigations - Sibarani, Andrew; Manullang, Herlina; Esther, July (Indonesian Journal of Law and Justice, 2024)
Tax law is a powerful tool to force taxpayers to comply with their tax obligations. This research uses descriptive analysis that describes the applicable laws and regulations related to criminal law policies in the application of the principle of restorative justice in tax criminal investigations. The purpose of tax audit is as a law enforcement effort by the Directorate General of Taxes (DGT) against taxpayers in carrying out tax obligations, which is based on the ultimum remedium principle that prioritizes administrative sanctions before criminal sanctions. It is expected that the tax education initiative will be able to improve the quality and effectiveness of tax education activities.